PENGARUH TAKARAN PUPUK SP 36 TERHADAP BIBIT JELUTUNG (Dyera lowii Hook) DENGAN INOKULASI MIKORIZA PADA MEDIA GAMBUT (Effect of Dosage SP 36 Fertilizer for Seed Jelutung (Dyera lowii Hook) with Mycorrhizal Inoculation on Peet Soil) - Burhanuddin . (Universitas Tanjungpura, 2011)
A study on the influence of of SP 36 dosage on jelutung (D.lowii Hook) seeds with mycorrhizal inoculation in the peat soils was conducted in a greenhouse Soil Science Laboratory Faculty of Agriculture, is Gadjah Mada University for 5 months in 2010. Research purpose was to determine was the dosage of fertilizer SP 36 can enhance the growth of jelutung seedlings inoculated with arbuskular mycorrhizal fungi. Nursery experiments were conducted using Completely Randomized Factorial Design with three replications. Observations made on jelutung seedlings 14 weeks of age after weaning include: height, diameter, number of leaves, shoot dry weight, and P uptake of plants after harvest. A dosage of SP 36 fertilizer of 100 ppm resulted in and the best increase of jelutung seedling growth in the nursery.ListenRead phonetically Keyword: Peatlang, mycorrhiza, Dyera lowii Hook, and SP 36